2009
DOI: 10.1515/mult.2009.002
|View full text |Cite
|
Sign up to set email alerts
|

Conversing through overlaps: Information status and simultaneous talk in Cuban Spanish

Abstract: Simultaneous speech and turn-taking patterns vary considerably across cultures. Research on varieties of Spanish has confirmed that frequent, lengthy overlaps within and between turns are common. In this paper it is suggested that when speakers engage in simultaneous talk, they observe Grice's Cooperative Principle by adjusting their utterances so that the informativeness of their contribution is minimized in overlap. This paper approaches the linguistic composition of overlaps by examining the information sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition to different class norms, the students followed different communication styles, which varied from culture to culture (Alfaraz, 2009). While they adhered to their own norms correspondingly, they evidently had different notions about how much participation in group discussions was "necessary" or appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to different class norms, the students followed different communication styles, which varied from culture to culture (Alfaraz, 2009). While they adhered to their own norms correspondingly, they evidently had different notions about how much participation in group discussions was "necessary" or appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In certain studies, interruptions and power relations correlate (Zimmerman & West, 1975;Zhao & Gantz, 2003;Minxia, 2010;Rodrigo, 2010). However, some studies have found that overlap, which is a type of interruption, can demonstrate cooperation in an interaction (Alfaraz, 2009;Jariah Mohd. Jan & Mohajer, 2012) rather than an expression of power.…”
Section: Turn-taking Interruption and Menmentioning
confidence: 99%
“…Jan & Mohajer, 2012) rather than an expression of power. Alfaraz (2009) explained that interactants cooperate with each other via overlaps in an effort to minimize the introduction of new information. In other words, the speakers overlap with the intention of supporting each other rather than to be informative.…”
Section: Turn-taking Interruption and Menmentioning
confidence: 99%